Trends in Arabic Language Course Program Management and its Relevance to Course Development: A Systematic Literature Review - Heriman, Heriman; Haryaka, Usfandi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Trends in Arabic language course program management continue to evolve in response to the increasingly dynamic learning demands of the globalization era. Amidst technological advancements and pedagogical transformations, course program management faces the challenge of remaining relevant and effective in addressing learners' needs. This study aims to analyze trends in Arabic language course management research through a systematic literature review. The main focus of the research includes three aspects: the main trends in Arabic language course management research, the strategies often used, and the relevance of these trends to future program development. Based on the analysis of 15 publications consisting of 13 journal articles, 1 master's thesis, and 1 undergraduate thesis, it was found that research trends concentrated on organizing, planning, implementing, evaluating programs, and using modern technology. Most of the studies used a descriptive qualitative approach to in-depth explore the internal dynamics of course institutions. The results show that frequently used management strategies include top-down approaches in organizing, integrated program planning, utilization of technology, innovative learning methods such as Mustaqili and Quality Function Deployment (QFD), and collaboration-based management. Moreover, the relevance of these trends to the future development of course programs confirms the importance of strategic planning, continuous evaluation, technology adoption, and visionary leadership to face global challenges. This research contributes to developing Arabic language course management theory and practice by offering strategic guidelines that educational institutions can implement.